The Influence Of Perceptions Of Organizational Support, Training, Self-Concept And Communication On The Work Effectiveness Of Employees Of The Regional Secretariat Of Muara Enim Regency - Hasmi Hasmi; Hardiyansyah Hardiyansyah; Fitriyah Fitriyah (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This research aims to identify and analyze the effect of perceptions of organizational support, training, self-concept and communication individually or collectively on the effectiveness of the employees of the Regional Secretariat of Muara Enim Regency. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test. Analysis using statistical calculations with multiple regression formula, partial test simultaneous test and the coefficient of determination. The results of the study explain that perceptions of organizational support have no significant effect on the effectiveness of the work of Regional Secretariat employees in Muara Enim Regency. Training has a significant effect on the effectiveness of the work of the Regional Secretariat of Muara Enim Regency Staff. Self- concept has no significant effect on the effectiveness of the work of Regional Secretariat employees of Muara Enim Regency. Communication has no significant effect on the effectiveness of the work of the Regional Secretariat of Muara Enim Regency. Perceptions of organizational support, training, self-concept and communication have no significant effect on the effectiveness of the work of Regional Secretariat employees of Muara Enim Regency.